Quantity of Antibiotic Use and Resistance Pattern of Gut Normal Flora Escherichia coli at Intensive Care Unit and Tropic Infection Ward, Dr Soetomo Hospital, Surabaya, Indonesia - Sholeh, Mohammad Akbaruddin; Kuntaman, Kuntaman; Hadi, Usman (Folia Medica Indonesiana, 2020)
Resistance to antibiotics is increasing worldwide, including in Indonesia. The use of antibiotics is the most common cause of microorganism resistance. Individuals who received antibiotic therapy impacton changes of normal micro-flora resistance through selective pressure. This study aims to analyze the relationship of the quantity of antibiotic use with the pattern of resistance of gut normal flora Escherichia coliamong patients in Intensive Care Unit (ICU) and Tropic Infection Ward, Dr. Soetomo Hospital, Surabaya. This study was cross-sectional design with 64 samples (32 the ICU and 32 in Tropic Infection Ward). The total sample were collected for three Months. Identification of intestinal microflora was done with McConkey differential selective medium, followed by IMViC biochemical test, and sensitivity test by antibiotic disc diffusion method. Data were analyzed with Chi square test and Fisher'sExact test. There was no significant difference (p=0.441) in the quantity of antibiotic use between ICU and Tropic Infection Ward. There was no significant difference (p>0.05) in normal intestinal flora Escherichia coli resistance pattern between Tropic Infection Ward and ICU against12 types of antibiotics. Ceftriaxone was the most widely used antibiotic in the Tropic Infection Ward of 54 DDD and ICU of 100 DDD. The highest percentage of intestinal flora Escherichia coli resistance at the ICU was ceftriaxone as manyas 18 (56.3%) and at Tropic Infection Ward on ciprofloxacin and levofloxacin 20 (62.5%). The other study in Primary Health center, showed that theresistance rates of both wards were significantly different as compared to intestinal flora of patients in primary health center (p <0.001), in whichthe use of antibiotics in primary health center was also lower (1.6 DDD). There was no significant difference (p>0.05) The pattern of bacterial resistance between patient with and without antibiotic use at Tropic Infection Ward and ICU Conclusion: the quantity of antibiotic use was not significantly different against resistnt gut flora between patients in ICU and Tropic Infection ward. The pattern of bacterial resistance between patient with and without antibiotic use was also not significantly different.